2017
DOI: 10.20944/preprints201703.0101.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Avian and Mammalian Facilitative Glucose Transporters

Abstract: Abstract:The GLUT members belong to a family of glucose transporter proteins that facilitate glucose transport across the cell membrane. The mammalian GLUT family consists of thirteen members (GLUTs 1-12 and HMIT). Humans have a recently duplicated GLUT member, GLUT14. Avians express the majority of GLUT members. The arrangement of multiple GLUTs across all somatic tissues signifies the important role of glucose across all organisms. Defects in glucose transport have been linked to metabolic disorders, insulin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Jejunum refers to the part of the small intestine that leaves the duodenum to one side, leading to the ileum, which is the primary purpose of the jejunum is to absorb monosaccharides, amino acids, and fatty acids, while the ileum absorbs the remnant nutrients that were not absorbed by the duodenum or jejunum, especially vitamin B12 and bile acids to be recycled (Collins et al., 2021 ). The glucose transporter families (Glut) and sodium‐dependent glucose transporters (Sglt) are responsible for the absorption of glucose, while the peptide transporters 1 and 2 are the members of the proton‐coupled oligopeptide transporter family and the Fatp1 mediates skeletal muscle cell fatty acid import (Byers et al., 2017 ; Guitart et al., 2014 ; Zwarycz & Wong, 2013 ). In a recent study, an HFD fed mouse with thyroid disorders for 16 weeks reported a significant reduction in Glut2, Pept1, and fatty acid translocase (FAT/CD36) expressions, indicating that HFD may impair nutrient intake in the small intestines (Torelli Hijo et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Jejunum refers to the part of the small intestine that leaves the duodenum to one side, leading to the ileum, which is the primary purpose of the jejunum is to absorb monosaccharides, amino acids, and fatty acids, while the ileum absorbs the remnant nutrients that were not absorbed by the duodenum or jejunum, especially vitamin B12 and bile acids to be recycled (Collins et al., 2021 ). The glucose transporter families (Glut) and sodium‐dependent glucose transporters (Sglt) are responsible for the absorption of glucose, while the peptide transporters 1 and 2 are the members of the proton‐coupled oligopeptide transporter family and the Fatp1 mediates skeletal muscle cell fatty acid import (Byers et al., 2017 ; Guitart et al., 2014 ; Zwarycz & Wong, 2013 ). In a recent study, an HFD fed mouse with thyroid disorders for 16 weeks reported a significant reduction in Glut2, Pept1, and fatty acid translocase (FAT/CD36) expressions, indicating that HFD may impair nutrient intake in the small intestines (Torelli Hijo et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%